The Spiritual Message of Mappalelo Cakkuriri Tradition: A Phenomenological Approach. - Masruq, Masruq; Khalik, Abdul; Said, Nurhidayat (Jurnal Mercusuar, 2020)
Puttada is a traditional village taken from the name of one of the nobles of the Sendana kingdom located in Sendana-Majene. The people of Puttada still maintain the customs and traditions inherited from their ancestors, such as the Mappalelo Cakkuriri tradition. The Mappalelo Cakkuriri ritual is a sacred procession that is held every four (4) years with various traditional ritual sequences. The Mappalelo Cakkuriri ritual reflects a complex spiritual message which involves unique communication events that involve certain communicative actions and specific meanings.